Nano- and micromaterials - Ohno, K. (Springer, 2017)
The future focus of nanotechnology will be on realizing new functions over greater scales. This book describes the creation of nano- and microscale structures and functions by controlling temperature, light, pressure, or carrier injections. It covers novel nano-integration technologies such as quantum-well devices possilbe by utilizing, for example, the self-organization of surface nanostructures and optically or pressure-induced phase transitions, micro machines using microstereolithography, as well as new techniques of laser spectroscopy and new computational methods for estimating atomic and electronic structures and their functions on the nano- and microscales.